Pengaruh Lingkugan Kerja Dan Pelatihan Kerja Terhadap Kinerja Karyawan PD. Artha Sanggraha Unit Usaha SPBU Shell Fatmawati Jakarta Selatan - Futri Nur Cahya; Ratnawaty Marginingsih (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Artha Sanggraha Shell Gas Station Business Unit its main activity is to distribute or sell fuel oil to the general public, especially for fueling people's or private vehicles. To find out how much knowledge the work environment and job training on employee performance. This study uses quantitative research methods using saturated sampling techniques to determine the effect between the three independent and dependent variables using descriptive methods in derived research data. Then research variables such as validity test, reliability test, normality test and classical assumptions are carried out. In testing the description of this data, researchers manage to find out the description or condition of the respondents who were sampled in this study. t value count 4.503> t table 2.00758, significant 0.00 <0.05 accepted. the value of t count 4,298> t table 310,883 significant 0.00 <0.05, accepted. all alpha Rhitung 0.05> Rtabel 0.2732 valid. the value of F count 310,883 F < table 3.18, significance 0.00 <0.05 valid. that work environment variables and job training together affect employee performance.